The impact of brainstorming on the achievement of the sixth grade students In the field of civic education and the development of their innovative penance - األـخاذ امىفاعػ امػكخِر ستار أضىػ عتػامؽضىي; الوػرس ـٔتثر رزكار رزاق (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The aim of this research was to find out the effect of brainstorming method on study achievement and creative thinking in civic education subject among sixth basic grade pupils. The researchers used quasi-experimental method with a backward test for academic achievement, with the pretest and post-test for creative thinking. The sample of the research consisted of (49) students equalized in some of the variables. An academic achieving test was prepared, consists of (46) items. The researchers found the validity and the reliability of the test by using coefficient equation of (KuderRichardson Formula (20)) which reached (0.70), beside they found the psychometric characteristic of the test. In order to measure the creative thinking, the researchers chose Torrance Form-B scale. After founding the validity and the reliability by using Cronbach Alpha, which reached (0.80). The experiment was conducted in first study course of the academic year (2013-2014), and lasted for 8 weeks. The results show significant differences in study achievement between both groups and in favor of experimental group at level of confidence 0.05. However, the results did not indicate any significant difference between female pupils as wells as male pupils in both groups. Nevertheless, significant differences were found between both groups in all creative thinking components (fluency, flexibility, originality, and details) in favor of experimental group. Though the results showed no significant difference among female pupils in both groups, significant difference was found between male pupils in creative thinking in favor of experimental group. After interpreting and analyzing the results the researcher presented some recommendations and suggestions. Key Words: Method, Brainstorming, achievement, Civic Educati